2022
DOI: 10.1038/s41598-022-24090-z
|View full text |Cite
|
Sign up to set email alerts
|

Green tea and coffee consumption and risk of kidney cancer in Japanese adults

Abstract: The study aimed to evaluate the association between green tea and coffee consumption and the risk of kidney cancer using data from a large prospective cohort study in Japan (the Japan Public Health Center-based Prospective Study: JPHC Study). A total of 102,463 participants aged 40–69 were followed during 1,916,421 person-years (mean follow-up period, 19 years). A total of 286 cases of kidney cancer (199 in men, 87 in women) were identified. Cox proportional hazards regression models were used to estimate haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The mechanisms underlying these protective effects involve modulation of signaling pathways such as the NF-κB signal pathway, TGFβ/p-ERK/p-Smad1/2 signal pathway, Nrf2 signaling activation, and autophagy restoration ( 112–117 ). Tea consumption has been associated with a reduced risk of renal cell carcinoma ( 118 ) and improved kidney function in diabetic patients ( 119 ). Studies indicate that effective components such as L-theanine, tea polyphenols, and EGCG can ameliorate renal cell damage through the modulation of related pathways, including the AGEs/RAGE signaling pathway ( 120 ), CYP450s/ROS/MAPK/NF-κB pathway ( 121 ), TGFβ/Smad3 signaling pathway ( 122 ), and ferroptosis ( 123 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying these protective effects involve modulation of signaling pathways such as the NF-κB signal pathway, TGFβ/p-ERK/p-Smad1/2 signal pathway, Nrf2 signaling activation, and autophagy restoration ( 112–117 ). Tea consumption has been associated with a reduced risk of renal cell carcinoma ( 118 ) and improved kidney function in diabetic patients ( 119 ). Studies indicate that effective components such as L-theanine, tea polyphenols, and EGCG can ameliorate renal cell damage through the modulation of related pathways, including the AGEs/RAGE signaling pathway ( 120 ), CYP450s/ROS/MAPK/NF-κB pathway ( 121 ), TGFβ/Smad3 signaling pathway ( 122 ), and ferroptosis ( 123 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding alcohol consumption, a study of Japanese men found that those who consumed ≥ 46 g and ≥ 69 g of alcohol per day had a respective 40% and 60% higher risk of developing cancer than those who consumed < 23 g of alcohol per day [ 5 ]. Diet, physical activity, and body weight control are suggested as important factors based on epidemiological evidence [ 6 - 9 ]. In Japan, the population-attributable fraction of cancer due to preventable factors is estimated to be about 55% for male and about 30% for female.…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of risk factors, such as infection with viral hepatitis, hepatic cirrhosis, obesity, and consumption of dietary hepatocarcinogens [ 8 , 9 ]. According to epidemiologic studies, it has been shown that regular tea consumption is associated with a decreased risk of various carcinomas, including breast cancer [ 10 ], bladder or kidney cancer [ 11 , 12 ], liver cancer [ 13 , 14 ], lung cancer [ 15 ], upper aerodigestive tract cancer [ 16 ], and others. Therefore, cancer prevention is of great significance.…”
Section: Introductionmentioning
confidence: 99%